2015
DOI: 10.1080/15384101.2015.1041683
|View full text |Cite
|
Sign up to set email alerts
|

The microtubule nucleation activity of centrobin in both the centrosome and cytoplasm

Abstract: Centrobin resides in daughter centriole and play a critical role in centriole duplication. Nucleation and stabilization of microtubules are known biological activities of centrobin. Here, we report a specific localization of centrobin outside the centrosome. Centrobin was associated with the stable microtubules. In hippocampal cells, centrobin formed cytoplasmic dots in addition to the localization at both centrosomes with the mother and daughter centrioles. Such specific localization pattern suggests that cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…We observed this association with both the endogenous centrobin protein and with GFP-tagged, overexpressed centrobin. Although centrobin has mainly been observed at daughter centrioles, it localized to both centrioles in cultured mouse hippocampal neurons ( Jeong et al, 2007 ; Gudi et al, 2011 ; Shin et al, 2015 ). Strikingly, we found that centrobin-deficient cells had a marked defect in forming primary cilia, which could be rescued by reexpression of centrobin ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed this association with both the endogenous centrobin protein and with GFP-tagged, overexpressed centrobin. Although centrobin has mainly been observed at daughter centrioles, it localized to both centrioles in cultured mouse hippocampal neurons ( Jeong et al, 2007 ; Gudi et al, 2011 ; Shin et al, 2015 ). Strikingly, we found that centrobin-deficient cells had a marked defect in forming primary cilia, which could be rescued by reexpression of centrobin ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It remains to be determined whether centrosome localization of centrobin is required for ciliogenesis. Appropriate regulation of microtubule stability is an obvious candidate mechanism by which centrobin may contribute to ciliogenesis ( Jeong et al, 2007 ; Gudi et al, 2011 ; Shin et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Centrobin, which is required for microtubule nucleation and stabilization (Gudi et al 2011), has been localized to the acroplaxome, marginal ring, manchette and centrosome during spermatogenesis (Liska et al 2009). A recent study demonstrated a specific localization for centrobin in the cytoplasm outside of the centrosome, which suggest a possible role as a microtubule nucleation site outside of the centrosome (Shin et al 2015). Centrobin C-terminal truncation results in decapitated sperm with head and tail malformations.…”
Section: Alternative Hypotheses For the Manchette Formationmentioning
confidence: 99%
“…Cdc6-depleted cells were incubated on ice for 1 h to depolymerize microtubules, followed by incubation at 37°C to allow microtubule regrowth (38). Microtubule regrowth from the centrosomes was measured for 15 s by immunostaining cells with either anti-␣-tubulin or anti-EB1 antibodies to detect microtubule formation (Fig.…”
Section: Cdc6 Depletion Increases Microtubule Regrowth Originating Frmentioning
confidence: 99%